Intraspecific Trait Variation and Coordination: Root and Leaf Economics Spectra in Coffee across Environmental Gradients - Isaac, Marney E.; Martin, Adam R.; de Melo Virginio Filho, Elias; Rapidel, Bruno; Roupsard, Olivier; Van den Meersche, Karel (Frontiers in Plant Science, 2017)
Hypotheses on the existence of a universal “Root Economics Spectrum” (RES) has received arguably the least attention of all trait spectra, despite the key role root trait variation plays in resource acquisition potential. There is growing interest in quantifying intraspecific trait variation (ITV) in plants, but there are few studies evaluating i) the existence of an intraspecific RES within a plant species, or ii) how a RES may be coordinated with other trait spectra within species, such as a leaf economics spectrum (LES). Using Coffea arabica (Rubiaceae) as a model species, we measured seven morphological and chemical traits of intact lateral roots, which were paired with information on four key LES traits. Field collections were completed across four nested levels of biological organization. The intraspecific trait coefficient of variation (CV) ranged from 25 to 87% with root diameter and specific root tip density showing the lowest and highest CV, respectively. Between 27-68% of root ITV was explained by site identity alone for five of the seven traits measured. Multiple factor analysis revealed significant orthogonal relationships between root and leaf spectra. A single principal component explained 56.2 % of root trait covariation, with plants falling along a RES from resource acquiring to conserving traits. RES traits were strongly orthogonal with respect to LES traits, suggesting these traits vary independently from one another in response to environmental cues. This study provides among the first evidence that plants from the same species differentiate from one another along an intraspecific RES. We find that in one of the world’s most widely cultivated crops, an intraspecific RES is orthogonal to an intraspecific LES, indicating that above and belowground responses of plants to managed (or natural) environmental gradients are likely to occur independently from one another.